2023
DOI: 10.1177/17474930231185468
|View full text |Cite
|
Sign up to set email alerts
|

A differential detailed diffusion-weighted imaging-ASPECTS for cerebral infarct volume measurement and outcome prediction

Abstract: Background Diffusion-weighted imaging-Alberta Stroke Program Early Computed Tomography Score (DWI-ASPECTS) has been used to estimate infarct core volume in acute stroke. However, the same and indiscriminate score deduction for punctate or confluent DWI-high-intensity lesion might lead to variation in performance. Aims To develop and evaluate a differential detailed DWI-ASPECTS method in comparison with the conventional DWI-ASPECTS in core infarct volume measurement and clinical outcome prediction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…For instance, it effectively forecasts the short-term prognosis of patients with acute ischemic stroke treated with iv-tPA [ 16 ]. Modified DWI-ASPECTS scores have shown superior correlation with volume estimation compared to conventional scores [ 17 ], and AI-based calculations have yielded results comparable to manual measurements by experienced neuroradiologists [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it effectively forecasts the short-term prognosis of patients with acute ischemic stroke treated with iv-tPA [ 16 ]. Modified DWI-ASPECTS scores have shown superior correlation with volume estimation compared to conventional scores [ 17 ], and AI-based calculations have yielded results comparable to manual measurements by experienced neuroradiologists [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a correlation between NIHSS and infarct volume in patients with acute stroke, but there are fewer reports on the degree of disability associated with ischemic volume and NIHSS score [ 17 , 18 , 19 , 20 ]. The aim of this study was to determine if the volume of ischemic lesions, as determined with DWI, was an independent predictor of the degree of disability.…”
Section: Introductionmentioning
confidence: 99%